2007
DOI: 10.1513/pats.200608-155ms
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art. Potential Etiologic Agents in Sarcoidosis

Abstract: The etiology of sarcoidosis remains uncertain. The hallmark of sarcoidosis is the epithelioid granuloma, which serves as a necessary starting point for considering disease etiology. Any etiologic agent of sarcoidosis must also explain the typical clinical behaviors and characteristic immunopathologic features of the disease. One clinical observation that serves as a bridge to the etiology of sarcoidosis is the Kveim reaction. In this reaction, local epithelioid granulomas develop several weeks after the intrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 15 publications
(14 reference statements)
1
48
1
3
Order By: Relevance
“…Although the aetiology of sarcoidosis remains uncertain [17], extensively conducted research has revealed several of the histopathologic and immunopathogenic events which occur during the development of noncaseating granulomas and might interpret the aforementioned redox imbalance [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Although the aetiology of sarcoidosis remains uncertain [17], extensively conducted research has revealed several of the histopathologic and immunopathogenic events which occur during the development of noncaseating granulomas and might interpret the aforementioned redox imbalance [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…(1,2) Although the disease is of unknown etiology, it is believed that there is an environmental agent, whether infectious or not, that is responsible for triggering the inflammatory response in genetically susceptible hosts. (1)(2)(3)(4)(5) The lung is the most commonly affected organ. (3,4,6) Although there is remission in 50% of cases, some patients live with chronic disease for decades.…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3)(4)(5) The lung is the most commonly affected organ. (3,4,6) Although there is remission in 50% of cases, some patients live with chronic disease for decades. (1,4) Sarcoidosis affects all ethnic and age groups, being more common before the age of 50 years and being predominant in females.…”
Section: Introductionmentioning
confidence: 99%
“…Sarcoidosis belongs to the group of diseases characterized by non-caseating epithelioid granulomas [1][2][3]. They consist of epithelial cells (activated macrophages) and Langhans' cells, occasionally containing Schaumann conchoid bodies and asteroid bodies [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…At its origin might lie infections, allergy, some medicines, chemicals, or autoimmune or genetic disorders [2,[5][6][7]. A predisposition towards sarcoidosis development was observed in subjects with HLA-B8 as well as HLA-B27 genotype [4,7].…”
Section: Introductionmentioning
confidence: 99%